Persuasion And Public Health Communication in Nigeria: Lessons From COVID-19 and Routine Vaccination Campaigns - Joyce Agbaka (PERSPEKTIF, 2026)
Public health crises have heightened the importance of persuasion and strategic health communication in shaping health-related behaviours. In Nigeria, persistent socio-cultural beliefs and structural disparities continue to influence health-seeking behaviour, particularly during pandemics such as COVID-19 and in routine vaccination programmes. This study examined the effectiveness of persuasive public health communication in Nigeria, drawing lessons from the COVID-19 pandemic and routine immunisation efforts. A qualitative research method was employed, relying on secondary data from existing scholarly literature. The Health Belief Model and Framing Theory guided the study. Findings indicate that effective public health communication significantly influences attitudes and behaviours toward vaccination, with clarity, consistency, trust, and cultural sensitivity emerging as key determinants of successful persuasion. Lessons from the COVID-19 experience highlight the need for strategic messaging in routine vaccination campaigns. The study concludes that the use of persuasive strategies, such as social influence, emotional appeal, and cognitive framing, can enhance vaccination uptake when integrated into culturally responsive public health communication.